2020
DOI: 10.1017/s1049023x2000117x
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual Consults by Paramedics to Reduce Hospital Transport After Low-Urgency Calls: Randomized Controlled Trial

Abstract: Introduction: The effect and subjective perception of audiovisual consults (AVCs) by paramedics with a distant physician in prehospital emergency care (PHEC) remain unexplained, especially in low-urgency calls. Objectives: The primary objective of the study was to evaluate the effect of AVCs by paramedics with a base physician on the rate of patients treated on site without the need of hospital transfer. The co-primary safety outcome was the frequency of repeated ambulance trips within 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…As in the Danish study, the causes of failure or difficulties were mainly related to the users’ handling of the smartphones or non-receipt/difficulty in accessing the SMS URL link. As with all published studies on the subject [ 17 , 27 , 28 , 30 ], acceptance of the video was excellent by both callers and physicians and was also considered easy to use.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…As in the Danish study, the causes of failure or difficulties were mainly related to the users’ handling of the smartphones or non-receipt/difficulty in accessing the SMS URL link. As with all published studies on the subject [ 17 , 27 , 28 , 30 ], acceptance of the video was excellent by both callers and physicians and was also considered easy to use.…”
Section: Discussionmentioning
confidence: 58%
“…However, this study does not prove an advantage of live video, as there was no control group for this subgroup. Furthermore, another study concluded in the COVID-19 context that the use of live video by emergency physicians was not superior to the use of the telephone alone [ 28 ]. Nevertheless, it seems that nurses/paramedics have difficulty in making an adequate “no transport” decision when they are sent to the patient [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study does not prove an advantage of live video, as there was no control group for this subgroup. Furthermore, another study concluded in COVID19 context that the use of live video by emergency physicians was not superior to the use of the telephone alone [28]. Nevertheless, it seems that nurses/paramedics have difficulty in making an adequate "no transport" decision when they are sent to the patient [29].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of virtual forward triage services that have been evaluated include small studies in the rural Czech Republic 6 and Denmark 7 demonstrated ‘treated and left on site’ rates of 16% and 29%, respectively, with mandated audio‐visual consult with emergency physicians. In the case of the Czech study, being treated and left at the scene following consultation was associated with a large proportion (19.6%) requiring repeat ambulance callout within 48 h.…”
Section: Virtual Forward Triagementioning
confidence: 99%